Snail Regulates MyoD Binding-Site Occupancy to Direct Enhancer Switching and Differentiation-Specific Transcription in Myogenesis - Soleimani, Vahab D. (Mol Cell, 2012)
In skeletal myogenesis, the transcription factor MyoD activates distinct transcriptional programs in progenitors compared to terminally differentiated cells. Using ChIP-Seq and gene expression analyses, we show that in primary myoblasts, Snail-HDAC1/2 repressive complex binds and excludes MyoD from its targets. Notably, Snail binds E box motifs that are G/C rich in their central dinucleotides, and such sites are almost exclusively associated with genes expressed during differentiation. By contrast, Snail does not bind the A/T-rich E boxes associated with MyoD targets in myoblasts. Thus, Snai1-HDAC1/2 prevent MyoD occupancy on differentiation-specific regulatory elements, and the change from Snail to MyoD binding often results in enhancer switching during differentiation. Furthermore, we show that a regulatory network involving myogenic regulatory factors (MRFs), Snai1/2, miR-30a, and miR-206 acts as a molecular switch that controls entry into myogenic differentiation. Together, these results reveal a regulatory paradigm that directs distinct gene expression programs in progenitors versus terminally differentiated cells.